(untitled) - Naterop, B. Jean (Cambridge, 2000)
Telephoning in English CD-ROM provides the intermediate level learner with a complete course which they can work through on their own to develop their skills in this vital area of business communication. The CD-ROM integrates content taken from the Telephoning in English Second Edition book and audio material to create an elegant and easy-to-use package for the self-study learner. Each of the eight units provides extensive listening and speaking practice as well as language reference sections which focus on the key exponents and exercises to practise form and function. The strength of the course lies in its systematic approach and uncomplicated structure. In total it provides about 20 to 25 hours of study.
Keywords: Telephone etiquette,English language,English language; Spoken english,Textbooks for foreign speakers